Mammalian Resilience Revealed by a Comparison of Human Diseases and Mouse Models Associated With DNA Helicase Deficiencies - Kohzaki, Masaoki (Frontiers in Molecular Biosciences, 2022)
Maintaining genomic integrity is critical for sustaining individual animals and passing on the genome to subsequent generations. Several enzymes, such as DNA helicases and DNA polymerases, are involved in maintaining genomic integrity by unwinding and synthesizing the genome, respectively. Indeed, several human diseases that arise caused by deficiencies in these enzymes have long been known. In this review, I present the DNA helicases associated with human diseases discovered to date using recent analyses, including exome sequences. Since several mouse models that reflect these human diseases have been developed and reported, I also summarize the current knowledge regarding the outcomes of DNA helicase deficiencies in humans and mice and discuss possible mechanisms by which DNA helicases maintain genomic integrity in mammals. I highlight specific diseases that demonstrate mammalian resilience, in which, despite the presence of genomic instability, patients and mouse models have lifespans comparable to those of the general population if they do not develop cancers; finally, I discuss future directions for therapeutic applications in humans that can be explored using these mouse models.